Representation of people who use drugs in Malaysian mainstream news reports / Ang Mei Hwa - Ang, Mei Hwa (2015)
People who use drugs (PWUD) are a marginalised group of people in Malaysia. They experience multiple denunciation including being homeless, having limited educational and career opportunities, experiencing fear and paranoia, having medical issues, being exposed to street violence, and learning to be helpless. While it is undeniable that PWUD (albeit not all) engage in crime to fuel their addiction and to survive, it is argued in this research that the relatively persistent engagement of semantic characterisations of PWUD in mainstream news perpetuates a societal conception that PWUD are dangerous pariahs. There are implications to these kinds of semantic propositions. These characterisations make it difficult for PWUD to be reintegrated into society as they reinforce existing stigmas, to break out of the aforementioned predicaments, to find stable jobs and to become useful members of society. This qualitative study examines a total of 77 mainstream news reports extracted from online archives to examine how the PWUDs’ identities are represented and established in the mainstream news reports, and (3) the possible theoretical explanations behind the construction of their identities with special focus on stigmatisation and ideologies that shape perceptions and mental representations. The findings of this study reveal that mainstream news reports represent PWUD with multiple identities through the employment of various linguistic elements and rhetoric devices. Through this realisation, this study provides possible alternatives that can be done to reduce stigma in the media against PWUD. Keywords: People who use drugs, semantic representation, identity, Malaysian news media, mainstream news, stigmatisation, ideologies, crime, discourse analysis.